2010
DOI: 10.3844/ajavsp.2010.86.90
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Stray Dogs with Intestinal Protozoan Parasites

Abstract: Problem statement: Intestinal protozoan parasites are important enteropathogens in dogs. Moreover, several canine intestinal protozoan parasites are zoonotic and are considered important to public health. This study investigates the level of intestinal protozoan parasites in stray dogs, in Kerman city, Iran. Approach: Determination of the prevalence of infections was based on faecal examination. Stool samples (n = 98) collected from dogs of different ages and gender were analyzed using five techniques, i.e., c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
3
2
3
1
Order By: Relevance
“…He also showed that the prevalence of Giardia spp of dog ranked the highest percentage (9%) followed by Isospora spp (7%) and Cryptosporidium spp (6%). Similar study was also found by Mohammad Mirzaei (2010) where he reported that the overall prevalence of parasitism was 13 (13.26%) dogs among 98 stool samples. The parasites most frequently detected were: Giardia spp (7.14%), Isospora spp.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…He also showed that the prevalence of Giardia spp of dog ranked the highest percentage (9%) followed by Isospora spp (7%) and Cryptosporidium spp (6%). Similar study was also found by Mohammad Mirzaei (2010) where he reported that the overall prevalence of parasitism was 13 (13.26%) dogs among 98 stool samples. The parasites most frequently detected were: Giardia spp (7.14%), Isospora spp.…”
Section: Resultssupporting
confidence: 85%
“…Mohammad Mirzaei (2010) where he reported that the giardia and coccidia infection was higher in female than male. Prevalence is variable and depended on a number of factors including age, living conditions, diagnostic methodology employed and region studied (Mundim et al, 2007).…”
Section: Prevalence Of Protozoan Diseases In Pet Dogsmentioning
confidence: 99%
“…The finding of infections with more than one enteric protozoa parasites is not surprising, and similar findings have been reported by various authors (Alvarado-Esquivel et al, 2015;Bahrami et al, 2011;Cantó et al, 2011;Adejinmi and Osayomi, 2010;Gingrich et al, 2010;Mukaratirwa and Singh, 2010;Gracenea et al, 2009;Nikolic et al, 2008). The prevalence of enteric protozoa parasites of dogs were significantly higher in free roaming and youger dogs .This finding is in agreement with Symeonidou et al (2017), Awadallah et al (2015), Adejinmi and Osayomi (2010) and Mirzaei (2010) who reported higher prevalence of protozoa parasites in younger dogs.…”
Section: Discussionsupporting
confidence: 88%
“…This is relatively high level of infection; and comparable to the report of Adejinmi and Osayomi (2010). This finding is higher than the reports from various areas: Martinez-Moreno et al 2007, Gingrich et al (2010), Mahmud et al (2014) and Mirzaei (2010) who reported 12.11%, 13.4%, 21.7% and13.26% from Spain, Galapagos Islands of Ecuador, Bangladesh and Iran, respectively. Such differences in the prevalence of enteric protozoa could be due to variation in geographic location, owners' awareness and the number of stray dogs' population in an area.…”
Section: Discussioncontrasting
confidence: 56%
“…However, dogs and cats can carry strains of Giardia which may be able to infect humans as well (Hopkins et al, 1997).In a recent study, the prevalence of Giardia spp. in stray dogs was found to be 7.14% (Mirzaei, 2010). Consequently, zoonotic transmission cannot be excluded, especially for immuno compromised people.…”
Section: Giardia Duodenalismentioning
confidence: 99%